Pengaruh Aplikasi Agensia Hayati pada Bibit Padi terhadap Perkembangan Penyakit Hawar Daun Bakteri dan Blas serta Pertumbuhan Tanaman Padi: English - Marwan, Husda; Mapegau, Mapegau; Mulyanti, Sri (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2018)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo), and the blast caused by Pyricularia oryzae can decrease rice production about 60% and 70%. The study aimed to determine the effect of rhizobacterial and endophytic bacterial isolates on BLB, blast, and the growth of rice plants, and also the characteristics of those biological agents. The isolates used were BR-IP3 dan BR-BC1 (bacterial isolates), BE-KR3 dan BE-KT2 (endophytic bacterial isolates). The rice varieties used Indragiri, Ciherang, and Inpara 3. The results showed that the application of various biological agents on rice seed of Indragiri, Ciherang, and Inpara 3 varieties were able to reduce the HDB of 80-100% and the blast of 31.8-88.6%. The isolates of BR-IP3 and BE-KR3 could dissolve phosphate and fix nitrogen, whereas the isolates of BR-BC1 and BE-KT2 were only able to dissolve phosphate.